Deception in environmental advertising: consumers’ reactions to greenwashing - Stokes, Staci Ann (Kansas State University, 2009)
The present research explored whether consumer reactions to a deceptive environmental ad differs from consumers’ reactions towards a similar true green ad. The deceptive ad used in this study violates all FTC regulations for acceptable environmental claims. The practice of deceptive environmental advertising, known as green washing, is an increasing problem for consumers and advertisers as environmental products and services are offered at an increasing rate in the marketplace. Undergraduate college students participated in the experiment testing four hypotheses. As predicted, consumers were not able to identify a green washed ad as deceptive. Similarly, a measurement of consumers’ perceived overall ethics associated with the ad revealed low ethical concerns towards both green washed and true green ads. Attitudes towards green washing were also measures, and, as hypothesized, consumers have equally positive attitudes towards green washed and true green ads and brands. Additionally, stronger levels of environmental concern decreased the consumers’ ability to detect deception in green washed ads. Implications indicate that consumers cannot perceive differences in green washed ads and true green ads, and the prevalence of green washing has the potential to cause serious damage to the credibility of the advertising industry.
Keywords: Greenwashing; advertising; Environment; green; Journalism (0391)